2022
DOI: 10.17576/jskm-2022-2001-15
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Occupational Therapy Handwriting Intervention for Children with Motor Coordination Issues: A Systematic Review

Abstract: Handwriting difficulty is one of the main issues among school children, especially for those with motor coordination issues. The aim of this systematic review is to evaluate the effectiveness of occupational therapy interventions in handwriting components for children with motor coordination issues. Current research articles were systematically searched according to the PRISMA guidelines. Two hundred and sixty-eight (n=268) research articles were identified; however, only ten (n=10) were eligible to be evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…From the systematic review by Zainol et al (2022) that investigated the effectiveness of occupational therapy handwriting interventions in children with motor coordination issues results showed that the method of the intervention had a big impact on how well handwriting skills were improved. The use of modern technology devices and application however did not improve handwriting performance (Coutinho et al 2016;Mcglashan et al, 2017).…”
Section: Cargot Et Al (mentioning
confidence: 99%
“…From the systematic review by Zainol et al (2022) that investigated the effectiveness of occupational therapy handwriting interventions in children with motor coordination issues results showed that the method of the intervention had a big impact on how well handwriting skills were improved. The use of modern technology devices and application however did not improve handwriting performance (Coutinho et al 2016;Mcglashan et al, 2017).…”
Section: Cargot Et Al (mentioning
confidence: 99%
“…Insufficient visual-motor skills resulted in reversal writing letters, lack of ability to copy a word from a visual board onto paper, missing letters during copying activity, and the absence of space between written words (5,6). In addressing these, literature supported that occupational therapy interventions such as biomechanical, neuromotor, cognitive, sensory integrative, compensatory and positive collaboration consultation approaches are effective to treat handwriting difficulty among children (4,(7)(8)(9)(10)(11). Many handwriting intervention foundation frameworks can be integrated to guide professional practice within a specific setting.…”
Section: Introductionmentioning
confidence: 99%